Integration of Employee Willingness and Team Learning: The Relationship Between Ambidextrous Leadership and Employee Creativity - Putu Pradiva Putra Salain; I Nengah Aristana; I Made Aditya Wardana (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – Employee creativity is a crucial capability required by organizations to maintain competitiveness and adaptability in an increasingly dynamic environment. However, the mechanisms explaining how ambidextrous leadership fosters employee creativity require further study, particularly in community-based financial institutions. This study aims to analyze the role of employee willingness and team learning as mediating variables in the relationship between ambidextrous leadership and employee creativity at Village Credit Institutions (LPD) in Bali. Design/methodology/approach – The research model examined the direct effect of ambidextrous leadership on employee creativity as well as its indirect effects through employee willingness and team learning. The results showed that ambidextrous leadership significantly increased employee willingness and team learning. Furthermore, employee willingness and team learning were shown to enhance employee creativity and act as mediators in the relationship between ambidextrous leadership and employee creativity. These findings indicate that employee creativity is not formed directly through leadership practices but rather develops through employees' willingness to contribute and through collective learning processes within the team Originality/Value – This research contributes to the growing literature on ambidextrous leadership by demonstrating that employee willingness and team learning are important mechanisms linking leadership practices to employee creativity. Practically, the findings suggest that LPD managers should strengthen employee participation and a culture of team learning to enhance organizational creativity and adaptability.